2010
DOI: 10.1213/ane.0b013e3181d31e91
|View full text |Cite
|
Sign up to set email alerts
|

In Normal Controls, Both Age and Gender Affect Coagulability as Measured by Thrombelastography

Abstract: Aging, female gender, use of OCs, and low-normal hematocrit levels have significant procoagulant effects. TEG measurements in native and recalcified citrated blood are not interchangeable, as indicated by differences between the 2 measurements ranging from 20% in maximal amplitude to 246% in clotting time. Furthermore, the limits of agreement strongly exceeded clinical acceptability to conclude interchangeability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
74
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 21 publications
10
74
0
4
Order By: Relevance
“…Female patients had higher MA levels than males (66.5 vs. 62.8, p < 0.001), which was consistent with Rafiq et al who reported that more female CABG patients presented with TEG-hypercoagulability and in healthy population female sex and older age are associated with hypercoagulability [6,20,21]. It has frequently been reported that women develop more severe strokes and have worse functional outcomes than men after ischemic stroke [22,23].…”
Section: Discussionsupporting
confidence: 83%
“…Female patients had higher MA levels than males (66.5 vs. 62.8, p < 0.001), which was consistent with Rafiq et al who reported that more female CABG patients presented with TEG-hypercoagulability and in healthy population female sex and older age are associated with hypercoagulability [6,20,21]. It has frequently been reported that women develop more severe strokes and have worse functional outcomes than men after ischemic stroke [22,23].…”
Section: Discussionsupporting
confidence: 83%
“…Three studies reported the extent of association between thromboelastometry/thromboelastography parameters and conventional coagulation assays [31][32][33]. The details are reported in table 2.…”
Section: Correlation With Conventional Parameters Of Hemostasismentioning
confidence: 99%
“…Two studies focused on thromboelastography [32,33]. In a study enrolling 120 participants (50% female) of 49.5 years on average, Roeloffzen and colleagues [33] compared R time with the aPTT, K time with the hemoglobin level, aPTT and the fibrinogen level, α angle with aPTT and the fibrinogen level, MA with the fibrinogen level, SEMS with the fibrinogen level, the CI with aPTT and the fibrinogen level, MTG with the fibrinogen level, TMG with aPTT, and the TTG with the fibrinogen level. Pearson's correlation coefficient was reported and varied between 0.21 (TMG vs. aPTT) and 0.40 (TTG vs. fibrinogen level).…”
Section: Correlation With Conventional Parameters Of Hemostasismentioning
confidence: 99%
“…7 These technologies have been used to verify the presence of hypercoagulability in pregnant and postpartum women [8][9][10] and have also been used to detect a positive association between blood hypercoagulability and age in non-obstetric patients. 11,12 Furthermore, previous non-obstetric studies have reported that hypercoagulable states detected by TEG are associated with an increased risk of thrombotic complications, including myocardial infarction and thromboembolic events. [13][14][15] Nevertheless, these technologies have not been used to investigate whether differences exist in the maternal coagulation profile of AMA vs non-AMA women during the peripartum period.…”
Section: Résumémentioning
confidence: 99%